Pengaruh Pemberian Fisioterapi Rutin Dan Neuromuscular Taping (NMT) Terhadap Penurunan Nyeri Pada Kasus Carpal Tunnel Syndrome (CTS) - Putri, Adhelia Megahayu; , Umi Budi Rahayu, S.Fis, M (2016)
Background: Carpal Tunnel Syndrome is a symptom due to compression of the median nerve as through the carpal tunnel. Physiotherapy routine using ultrasound modality that provides sedative and analgesic effect on sensory nerve endings so that the pain is reduced and Transcutaneus Electrical Nerve Stimulation resulting in a small motor afferent activity ergoreseptor that led to the activation of the course of inhibition of pain. NeuroMuscular Taping (NMT) is a technique that involves the use of elastic adhesive tape on the skin that provide a local therapeutic effect by using decompression techniques that can lead to wrinkle. Objective: Knowing effects of physiotherapy routine and neuromuscular taping (NMT) to the reduction of pain in case of Carpal Tunnel Syndrome (CTS). Methods: This research is a quasi experiment with two group pre test and post test design, the sample group given physiotherapy routine and group II was given NeuroMuscular Taping (NMT) for 4 weeks with a frequency 2x a week. Pain was measured by visual analogue scale. Data analysis using Wilcoxon test to test the effect and of different test using Mann Whitney test. Results: There was an effects of physiotherapy routine after the performed statistical tests obtained using Wilcoxon test p-value of 0,007. There was an effects of NeuroMuscular Taping (NMT) are the result of p-value of 0,005, and there are differences in the effect after using statistical test Mann Whitney test was obtained p-value of 0,000. Conclusion: There was an difference between the effect of giving physiotherapy routine and NeuroMuscular Taping (NMT).